Fundamentación Conceptual De Una Semiótica De La Cultura a Partir Del Proyecto Teórico De I.M. Lotman - Brower Beltramin, Jorge (Re-presentaciones: Periodismo, comunicación y sociedad, 2008)
The objective of this review is to expose the theoretical project proposed by I.M. Lotman of being able to articulate a semiotic of the culture to give account of diverse objects of study that are expressed like complex sign systems. In such sense we included the contribution of Lotman related to the contextual conditions and structural qualities of these systems as well as conditioners that must be gotten up to enrich the analytical approaches of semiotic nature. On the other hand, the project of Lotman ties here, with the most excellent contributions of the constructivist paradigm, reinforcing the epistemology position of base from which the semiotics processes in study must be included/understood.
Keywords: Semiotic; Culture; Epistemology; Constructivism